DESIGN AND REALIZATION OF WEARABLE ULTRAWIDEBAND ANTENNA TRIANGULAR PATCH FOR HEALTH APPLICATIONS WITH DEFECTED GROUND STRUCTURE METHODS - HARFAN HIAN RYANU; Ruben Samuel Marojahan Purba; FARDAN FARDAN; Levy Olivia Nur; Bambang Setia Nugroho (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2022)
Wearable antenna is currently a very popular topic because it has the advantages of small size, light weight, and flexible shape. Because of their versatility, wearable antennas are often used in healthcare, as well as military applications. In this research, a wearable triangular patch antenna is designed at the Industrial, Scientific, Medical (ISM Band) 2.4 GHz frequency using Cordura Delinova 2000 textile as a substrate and copper tape as a conductor for the patch and ground plane. To obtain ultra-wideband characteristics, the Defected Ground Structure technique is used. From the simulation results carried out under normal conditions, a bandwidth of 1403.9 MHz is obtained with a VSWR value of 1.004 and a gain of 2.355 dBi. By adding a phantom with hand characteristics, the simulation results show a bandwidth of 1354.1 MHz, VSWR 1.36, Gain 7.35 dBi, and SAR 0.4 W/Kg at a distance of 30 mm from the phantom. From the measurements made under normal conditions, a bandwidth of 684.3 MHz, a VSWR of 1.1045 and a gain of 2.01 dBi are obtained. From the on-body measurement using wrist, the antenna obtains a bandwidth of 615.2 MHz and VSWR of 1.4027, at a distance of 30 mm from the phantom. Based on the parameters obtained in the measurement and simulation, the antenna can be used in the 2.4 GHz frequency.